Guarantee contracts in Islamic financial transaction: analysis of BNM resolution and AAIOFI standards - Busari, Saheed Abdullahi; Suleiman, Hassan; Salhab, Belal Barakat Sulaiman (USIM Press, 2024)
A guarantee (Kafalah) is considered an effective Islamic finance contract aimed at providing assurance and security by having a third party, the guarantor, commit to fulfilling the debtor's financial obligations in case of default. However, the Bank Negara Malaysia (BNM) policy document considered the guarantee as kafalah, while the Accounting and Auditing Organization for Islamic Financial Institutions (AAIOFI) considered it Damān. The term guarantee falls within the category of non-compensatory contract in classical Islamic financial contracts whereby there are no returns or compensation available for contracts like benevolence loans (Qard), gifts (Tabarru/Hibah), guarantee (Kafalah), and assignment of debt (Hawalah). In the modern financial setting, this might not fulfil one of the objectives of Islamic financial institutions, which is to offer services for profit. This study explores the application of Guarantee (Kafalah) as a non-compensatory and noncommutative contract, falling under the category of Uqud Ghair Mua’wadha in Islamic Financial Institutions. This study uses the doctrinal approach of the qualitative method in exploring juristic meaning, justification, and implications of the shariah terms. It analyses the sustainable implication of its application in contemporary Islamic finance institutions between BNM and AAIOFI. This study found that despite the classical implication of guarantee as a non-compensatory contract guarantee, contracts cannot yield a direct profit. However, they can generate income through Wakālah (agency fee), such as issuing LCs guarantees. These may be charged based on expenses incurred in amount-based (possibly slabs) but not time-based structures. The finding shows that the comparative analysis of regulatory frameworks by BNM and AAIOFI underscores the challenges of harmonizing global standards with local contexts, highlighting the necessity for ongoing dialogue and collaboration to ensure coherence and adaptability in Islamic finance regulation.